Protocolo para la adaptación en infraestructura y dotación de los servicios de UCI y urgencias de una unidad hospitalaria temporal durante emergencia sanitaria en Colombia - Enciso Cortes, Karen Lizeth (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
This directed work is focused on the creation of a clinical protocol that serves as a guide of good practices in the process of opening a temporary hospital unit. It has been developed in compliance with the Ministry of Health and Social Protection together with the National Institute of Health in Colombia, within the framework of generating a plan of preparation and early response to multi-risk scenarios for the standards of equipment and infrastructure. Making available to the health personnel, a proposal of methodology and tools that facilitate the elaboration of their own institutional plans. Forms and some case studies are presented to help the user better interpret the content of the publication, which can be modified or adapted according to the specific requirements of each institution.

Este trabajo dirigido está enfocado en la creación de un protocolo clínico que sirva como guía de buenas prácticas en el proceso de abrir una unidad temporal hospitalaria. Ha sido elaborado acatando lo establecido por el Ministerio de Salud y Protección Social junto con el Instituto Nacional de Salud en Colombia, en el marco de generar un plan de preparación y respuesta temprana ante escenarios multirriesgo para los estándares de dotación e infraestructura. Poniendo a disposición del personal de salud, una propuesta de metodología y herramientas que faciliten la elaboración de sus propios planes institucionales. Se presentan formularios y algunos casos prácticos que ayuden al usuario a una mejor interpretación del contenido de la publicación, los cuales pueden ser modificados o adaptados según los requerimientos específicos de cada institución.
Protocol for the adaptation in infrastructure and equipment of the UCI and emergency services of a temporary hospital unit during health emergencies in Colombia
Keywords: Dotación; Emergencia sanitaria; Infraestructura; Plan de respuesta; Unidad Hospitalaria Temporal; Equipment; Health emergency; Infrastructure; Response Plan; Temporary hospital unit